T.S.Eliot’s Influence on the Theme of Spiritual Crisis in Modern Uzbek Poetry (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
T.S. Eliot’s poetry frequently explores themes of spiritual crisis, disillusionment, and the search for meaning in a fragmented world. His works, particularly The Waste Land and Four Quartets, reflect a struggle with faith, tradition, and modern existence. This study examines how similar themes appear in modern Uzbek poetry, particularly in the works of Abdulla Oripov, Erkin Vohidov, and Chulpon. While there are no direct translations of Eliot’s poetry into Uzbek, his influence has reached Uzbek literature through Russian and Western literary traditions. This article explores Eliot’s legacy in shaping spiritual and existential themes in Uzbek poetry, demonstrating how modern Uzbek poets engage with questions of faith, identity, and cultural disillusionment.